Diffuse Low-Grade Gliomas in Adults Natural History, Interaction with the Brain, and New Individualized Therapeutic Strategies - Duffau, Hugues (Springer London : Imprint: Springer, 2013)
The biology, behavior and management of diffuse low-grade gliomas (DLGG) in adults have been matters of controversy for many decades.  However, recent technical and conceptual advances in genetics, imaging and treatments have paved the way towards individualized management. In addition, advancing knowledge of brain processing means that it is possible to take into consideration the interaction between the disease (low-grade glioma) and the host (the brain) and thus to modulate the therapeutic strategies with the goal to increase the median survival as well as to improve the quality of life.   Diffuse Low-Grade Gliomas in Adults: Natural History, Interaction with the Brain, and New Individualized Therapeutic Strategies presents the latest research pertaining to the diagnosis, therapy and management of diffuse low-grade gliomas (DLGG) in adults, with a particular focus on the path towards individualized therapy for this kind of tumor.  Recent research on the natural history of DLGGs and their interaction with the brain has led to new diagnostic and therapeutic strategies which increase survival and quality of life of the patient, and these methods are described in this book.   This book uniquely focuses on addressing diffuse low-grade gliomas in adults and is a valuable resource for medical oncologists, neuro-oncologists and neurologists.